2020
DOI: 10.3390/en13020480
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Solid Fuel Hydrochar over Hydrothermal Carbonization of Red Jujube Branch

Abstract: Biomass energy is becoming increasingly important, owing to the decreasing supply of fossil fuels and growing environmental problems. Hydrothermal carbonization (HTC) is a promising technology for producing solid biofuels from agricultural and forestry residues because of its lower fossil-fuel consumption. In this study, HTC was used to upgrade red jujube branch (RJB) to prepare hydrochar at six temperatures (220, 240, 260, 280, 300, and 320 °C) for 120 min, and at 300 °C for 30, 60, 90, and 120 min. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Compared with the initial feedstock, the HHV of PPHC increased by 32%-46%, indicating that HTC is an effective method for producing solid fuels with high energy density. 31,33,34 The HHV of PLBC was much lower than that of PPHC, ranging between 15.5 and 18.8 MJ kg -1 . This was comparable with the values reported in a previous study, where an HHV value of 18.9 MJ kg -1 was obtained from poultry litter torrefied at 300 °C.…”
Section: Physicochemical Properties and Structural Characteristicsmentioning
confidence: 97%
“…Compared with the initial feedstock, the HHV of PPHC increased by 32%-46%, indicating that HTC is an effective method for producing solid fuels with high energy density. 31,33,34 The HHV of PLBC was much lower than that of PPHC, ranging between 15.5 and 18.8 MJ kg -1 . This was comparable with the values reported in a previous study, where an HHV value of 18.9 MJ kg -1 was obtained from poultry litter torrefied at 300 °C.…”
Section: Physicochemical Properties and Structural Characteristicsmentioning
confidence: 97%
“…Hydrothermal carbonization (HTC) is a thermochemical reaction-based method which occurs in a relatively low temperature range (150-300 • C) with moisture and autogenous pressure [9,10]. The relatively low energy input and mild treatment conditions of HTC have caused it to receive attention as an alternative biomass treatment technology rather than conventional thermal treatment technologies (e.g., pyrolysis, combustion) [11,12]. During the HTC reaction, various types of organic matter are converted into a valuable carbon-rich material (i.e., hydrochar).…”
Section: Introductionmentioning
confidence: 99%
“…For the above reason, considerable studies on HTC reactions for hydrochar production and its use as a solid fuel have gained significant interest in this research area. Li et al and Roy et al reported on potential routes for solid fuel production using hydrochar derived from red jujube branch and peat moss, respectively [12,17]. Not only experimental research but also process efficiency modeling and cost analysis studies on HTC reactions have been published.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have conducted extensive studies on different lignocellulosic biomass types by HTC treatment, including glucose [12], cellulose [13], rice straw [14], edible cactus cladodes [15], water hyacinth [16], coconut and rice husks [6], red jujube branches [17], and waste eucalyptus barks [18], and so on. The hydrothermal operating conditions, including the reaction pressure [8], reaction temperature [9], residence time [9], reaction solution [19], solid/liquid ratio [15], mixing [20], catalyst (residual liquid of HTC, acid or alkali solutions) [21], and particle size [22], have various influences on the properties of the HTC products.…”
Section: Introductionmentioning
confidence: 99%